Profiling the Research Landscape on Cognitive Aging: A Bibliometric Analysis and Network Visualization - Othman, Zahiruddin; Abdul Halim, Ahmad Shahril; Azman, Khairunnuur Fairuz; Ahmad, Asma Hayati; Zakaria, Rahimah; Sirajudeen, Kuttulebbai Nainamohamed Salam; Wijaya, Adi; Ahmi, Aidi (Frontiers in Aging Neuroscience, 2022)
Objectives This study aimed to profile the cognitive aging research landscape from 1956 to 2021. Methods A total of 3,779 documents were retrieved from the Scopus database for the bibliometric analysis and network visualization. By comparing each keyword’s overall connection strength (centrality), frequency (density), and average year of publication (novelty) to the calculated median values acquired from the overlay view of the VOSviewer map, the enhanced strategic diagrams (ESDs) were constructed. Results The findings showed an increasing trend in the number of publications. The United States leads the contributing countries in cognitive aging research. The scientific productivity pattern obeyed Lotka’s law. The most productive researcher was Deary, I. J., with the highest number of publications. The collaborative index showed an increasing trend from 1980 onwards. Frontiers in Aging Neuroscience is the most prestigious journal in the field of cognitive aging research. In Bradford core journals zone 1, the top 10 core journals of cognitive aging research provided more than half of the total articles (697, or 55.36 percent). Conclusions For the next decades, the trending topics in cognitive aging research include neuropsychological assessment, functional connectivity, human immunodeficiency virus (HIV), decision-making, gender, compensation, default mode network, learning and memory, brain-derived neurotrophic factor (BDNF), obesity, D-galactose, epigenetics, frailty, mortality, mini-mental state examination (MMSE), anxiety, and gait speed.